2018
DOI: 10.1016/j.prosdent.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistance and abrasiveness of CAD-CAM monolithic materials

Abstract: The nanofilled composite resin and polymer-infiltrated ceramic were more antagonist-friendly (whether enamel or CAD-CAM material) than glass-ceramics and zirconia. Care should be taken when selecting the material that will contact mainly with glass-ceramics. Hardness should also be considered when selecting a material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 27 publications
11
99
0
10
Order By: Relevance
“…This is a benefit for the antagonist's teeth because it produces less wear. Differences in surface roughness of materials were also found in a similar study [54]. These results show that mechanical polishing can result in lower Ra and Rz values before and after thermocycling, resulting in reduced microbial adhesion.…”
Section: Discussionsupporting
confidence: 80%
“…This is a benefit for the antagonist's teeth because it produces less wear. Differences in surface roughness of materials were also found in a similar study [54]. These results show that mechanical polishing can result in lower Ra and Rz values before and after thermocycling, resulting in reduced microbial adhesion.…”
Section: Discussionsupporting
confidence: 80%
“…Ludovichetti et al (15) used two-body wear test with ACTA wear machine for 200,000 cycles and determined the wear rate with a surface profilometer. The authors did not found statistically difference between ZLS and LD for wear against bovine enamel.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens were then individually embedded in autopolymerizing acrylic resin cylinder, leaving the top of each disc uncovered. Thus, the samples were submitted to the wear simulator (Biocylce V2, Biopdi, São Carlos, SP, Brazil) with 2 mm steatite pistons (magnesium silicate, Ceramica Chiarotti, Jaguariúna, SP, Brazil), which served as analogue to dental enamel antagonist (15)(16)(17). The wear simulator operates by applying a vertical load on the specimen, sliding horizontally, and then repeating the cycle (16).…”
Section: Wear Simulationmentioning
confidence: 99%
“…In addition, the adhesive bond between the veneer layer and the zirconia coping allows the use of polymer‐containing materials, such as the PIRGN tested here, and also of conventional resin composite CAD/CAM blocks. The combination of a stiff zirconia framework with a resin composite veneer has shown a mechanical performance comparable with that of glassy veneers but reduced wear on the enamel antagonist . On the other hand, this technology faces important esthetic limitations as a result of the monochromatic color features of the CAD/CAM blocks.…”
Section: Discussionmentioning
confidence: 99%